H.P. Lovecraft and Posthumanism - Horváth, Márk (Critical Posthumanisms, 2026)
The present book is the first monograph detailing the intriguing connections between H. P. Lovecraft's weird fiction and posthumanism. More than a retrospective reinterpretation, H. P. Lovecraft and Posthumanism enacts a productive dialogue between Lovecraft's "cosmic indifferentist" philosophy and contemporary post-anthropocentrism. In more ways than one, Lovecraft's literary and philosophical output alike presaged our contemporary era, one in which the primacy of the human is becoming open to question. The crisis-ridden darkness we face today is revealed as signalling the advent of the posthuman "strange aeon," the Age of Lovecraft.